2021
DOI: 10.1111/ane.13495
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene‐related peptide‐induced hemodynamic changes in migraine with and without aura

Abstract: Objectives Exogenous calcitonin gene‐related peptide (eCGRP) can induce CGRP‐induced headaches (CGRP‐IH) and aura in migraine with aura (MA). This implies a common pathophysiological mechanism of trigeminovascular sensitization (TVS) in migraine headaches and aura. The aim was to assess hemodynamic changes in cerebral circulation induced by eCGRP. We predicted that cerebral hemodynamic changes may differ between migraine without aura (MO) and MA. Materials and methods We included twenty participants with migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…One study found an increase of MABP with 11% after CGRP. The mean V MCA was decreased with 9.5%-21% (11,15,16,19,21) and the diameter of the STA was dilated with 41%-43%. Based on the blood flow velocity decrease, Lassen et al (16) estimated the dilation of the MCA to be 7.5%, given that the total blood flow is constant.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…One study found an increase of MABP with 11% after CGRP. The mean V MCA was decreased with 9.5%-21% (11,15,16,19,21) and the diameter of the STA was dilated with 41%-43%. Based on the blood flow velocity decrease, Lassen et al (16) estimated the dilation of the MCA to be 7.5%, given that the total blood flow is constant.…”
Section: Resultsmentioning
confidence: 92%
“…The database search identified 386 citations after removing duplicates. Through manual screening of title, abstract and full text review of relevant articles, 11 studies met the inclusion criteria and were included in Scheme 1 (11,12,(15)(16)(17)(18)(19)(20)(21)(22)(23). Data following infusion of h-α-CGRP, but not placebo, was included (Tables 1-3).…”
Section: Resultsmentioning
confidence: 99%
“…On the other side, an enhanced response of vm MCA is observed in migraine with a positive relationship between vm MCA responses and migraine (11). According to the previous explanation, hemodynamic changes in cerebral circulation after CGRP infusion are attributed to an enhanced vasodilatation of proximal large arteries in migraine (12). Thus, the vm MCA can be used for discrimination of migranous susceptible to CGRP from others, migranours and non-migranours.…”
Section: Methodology For Cgrp Testingmentioning
confidence: 88%
“…A recent scientific concept predicted CSD as an initial event for trigeminal activation, but it does not explain the connection between CGRP and the aura ( 7 ). In our previous works, we used exogenous CGRP to provoke a hemodynamic response in the anterior and posterior cerebral circulations ( 8 , 9 ). The hemodynamic responses of MCA and PCA were used because we considered them as indicators of neural activity and sensitization during migraine attacks due to the trigeminovascular reflex (TVR).…”
Section: Introductionmentioning
confidence: 99%
“…The hemodynamic responses of MCA and PCA were used because we considered them as indicators of neural activity and sensitization during migraine attacks due to the trigeminovascular reflex (TVR). In the first study, we did not explore the magnitude of the hemodynamic responses separately for migraine with aura (MA) and migraine without aura (MO), but the results of our recent study suggest differences in the vascular responses between MO and MA ( 9 ). However, it is still not clear whether MO and MA show differences in the response's magnitude in the anterior and posterior cerebral circulation.…”
Section: Introductionmentioning
confidence: 99%